Annual vaccine-preventable disease report for New South Wales, Australia, 2014 - Nathan Saul; Robin Gilmour; Paula Spokes (World Health Organization Regional Office for the Western Pacific, 2017)
This report provides an epidemiological description of selected vaccine-preventable diseases in New South Wales (NSW), Australia, for 2014 to inform ongoing disease monitoring and control efforts. A trend of increasing pertussis notifications was observed, beginning midway through 2014 with the highest disease rates in the 5-9 year age group. Measles notifications increased to 67 cases in 2014 from 34 cases in 2013. Measles cases were associated with travel-related importations-predominantly from the Philippines-and secondary transmission increased compared to 2013 involving three main disease clusters. Notifications of invasive meningococcal disease continued to decline across the state with meningococcal B remaining the most common serogroup in NSW. Increasing rates of pertussis notifications from mid-2014 may indicate the beginning of an epidemic, ending the period of low transmission observed in 2013 and the first half of 2014. An increase in measles notifications in 2014, including secondary transmission, indicates the continued need for public health actions including robust follow-up and awareness campaigns.